Cladistic analysis of self-grooming indicates a single origin of eusociality in corbiculate bees (Hymenoptera: Apidae) - Canevazzi, Naila Cristina de Souza [UNESP]; Noll, Fernando Barbosa [UNESP] (Wiley, 2015)
Behavioural traits have been used extensively in recent years as an important character source for making phylogenetic inferences. The phylogenetic positions of the members of the Apini subtribe are increasingly being debated, and new characters must be examined. We analysed the presence and absence of certain behavioural patterns, as well as the sequences of some of these patterns, to generate 79 characters. Eleven species comprised the ingroup, and Xylocopini comprised the outgroup. Parsimony analysis showed that the most parsimonious tree was (Euglossina(Bombina(Apina+Meliponina))). This topology is consistent with most studies that use morphological data and the few that use behavioural data, which suggests that advanced eusociality arose only once in a common ancestor of the clade Apina plus Meliponina; however, this hypothesis is inconsistent with our molecular data. Thus we considered behavioural, molecular, and morphological data and recovered the same topology, in which eusociality has a single origin in corbiculate bees.